Dimensions of well-being and social harmony of older persons in Ghana: A secondary analysis of longitudinal survey data of the 2014/15 Study on Global Ageing and Adult Health (SAGE Wave 2). - Joseph Kojo Oduro; Akwasi Kumi-Kyereme (PLoS ONE)
Objectives A crucial factor in healthy ageing is age-friendly environments for older persons. The opportunities that come with getting older as well as the safety of older persons are influenced by their social surroundings and overall well-being, yet, there is a dearth of research focus on this subject. This study examined the association between dimensions of well-being and the social harmony of older persons in Ghana. Methods A secondary analysis of longitudinal survey data of the 2014/15 Study on Global Ageing and Adult Health (SAGE Wave 2) conducted by the World Health Organization was used. Only older adults 60 years and older were included in this study. Multilevel logistic regression techniques were used to examine dimensions of well-being as predictors of social harmony of older persons. The output was reported as odds ratios (OR). Results Results show that high levels of emotional and physical well-being were 13.5% and 14.3% more likely to be associated with a high level of social harmony (OR = 1.35, 95% CI = 1.35,1.35), (OR = 1.43, 95% CI = 1.43,1.43). However, older persons with high levels of psychological and spiritual well-being were 7% and 3% less likely to experience a high level of social harmony (OR = 0.73, 95% CI = 0.63,0.93), (OR = 0.39, 95% CI = 0.39,0.40). Conclusion This study shows a multifarious association between dimensions of well-being and the social harmony of older persons. A positive association is found between high levels of emotional and physical well-being and social harmony in older persons. However, older persons with high levels of psychological and spiritual well-being showed less experience of social harmony. This has implications for policy for improving older persons' well-being and social harmony. Policies and social interventions should consider the various needs and situations of older persons to establish an environment of safety and opportunities concerning higher social harmony in Ghanaian society.